Creating context: Ethnography and local concept „both a man and a woman“ in the Roma community in Skopje - Ines Crvenkovska-Risteska (University of Belgrade, 2016)
The research in this text focuses on creating a research context, which reflects the notion of sexuality of individuals born as male and feeling as „women“ or „as both male and female“ in the Roma community in Skopje. The ethnographic „field“ is created nontraditionally and reflects the characteristics of the local sex/gender „both male and female“ concept, which leads to the systemic characteristics in the local economies where sexuality acquires an economic form.